Organizational Culture Change and Adaptation in the Face of Digital Transformation: A Study of Jambi’s Banking Sector - Handani, Deni (Enigma in Economics, 2024)
The advent of digital transformation has necessitated significant changes in organizational culture and adaptation strategies, especially within the banking sector. This study aims to examine the impact of digital transformation on organizational culture change and adaptation within the banking sector in Jambi, Indonesia. A mixed-methods approach was employed, incorporating both qualitative and quantitative data collection and analysis techniques. Semi-structured interviews were conducted with key stakeholders within the banking sector in Jambi, including bank managers, employees, and customers. Additionally, a survey was administered to a larger sample of bank employees to gather quantitative data on their perceptions of organizational culture change and adaptation in the face of digital transformation. The findings of this study indicate that digital transformation has had a profound impact on organizational culture change and adaptation within the banking sector in Jambi. The study revealed that banks that were successful in adapting to digital transformation were those that had a strong culture of innovation, collaboration, and customer-centricity. These banks were also more likely to have invested in employee training and development programs to equip their workforce with the necessary skills to navigate the digital landscape. In conclusion, this study provides valuable insights into the challenges and opportunities associated with organizational culture change and adaptation in the face of digital transformation within the banking sector. Additionally, investing in employee training and development is crucial for ensuring that the workforce is equipped with the necessary skills to thrive in the digital era.